Cyclical Fiscal Rules for Oil-Exporting Countries - Snudden, Stephen (IMF Working Papers; Working Paper ;, 2013)
Structural budget-balance rules with countercyclical elements appear well suited to stabilize the macroeconomic volatility of oil-exporting countries and have been used successfully by other commodity exporters. Using a global DSGE model, the efficient design of such rules is found to depend on the source of oil price fluctuations and the oil exporters' structural characteristics. The output-inflation tradeoff is of particular concern for oil exporters relative to non-oil exporters due to the pass through of oil prices into headline inflation. Fiscal rules are best when coordinated with inflation targeting monetary policy, but are still desirable for fixed exchange rate regimes.